The Acceptance Level Of Electronic Government Initiatives At The Tripoli Immigration Department Of Libya - Alkeshar, Faisal Muftah Ahmad (2008)
This study was to find out whether the acceptance level of electronic government initiatives at the Tripoli immigration department of Libya. This study is designed to provide the benefit for practitioners, especially for employees and management position in immigration department to using the electronic government for their work. The study found that there are positive relationship between technology acceptance model (ease of use and usefulness) and electronic government initiatives.